Stratigraphic architecture and evolution of a barrier seagrass bank in the mid-late Holocene, Shark Bay, Australia - Bufarale, G.; Collins, Lindsay (Elsevier, 2015)
Within the Faure Sill complex (Shark Bay, Western Australia), a combination of remote sensing analysis, seismic stratigraphy and cores to ground truth, together with radiocarbon dating, demonstrate the interconnection between sediment body morphologies, seagrass related substrates and pre-existing topography and reveal the system as a channel–bank complex. Sea level fluctuations appear to have largely controlled the hydrodynamic conditions of the bank, contributing to each stage of its evolution. 1) Not earlier than 8.5–8.0 ka BP, in a lowstand period, after an erosive event of underlying palaeosurfaces, seagrass establishment progressively contributed to initiating bank growth. 2) Around 6800 years BP, bank accumulation reached its apex, in conjunction with a rapid sea transgression. 3) During the Late Holocene, succeeding a slow decline to present sea level, bank growth continued to fill available accommodation space and a number of hiatuses, indicating temporal and spatial discontinuities within the process of bank building, are recognised. Average depositional rates of bank building (1.3 m/ka) conform to previous estimates derived for seagrass banks but rates are strongly facies dependent, attesting to the dynamic nature of this channel–bank complex. The extensive seagrass meadows are essential for a wide range of aspects of the environment of the Shark Bay area. Not only are they particularly important for the entire shallow benthic ecosystem, but they also had a major role in the partial closure of the southern basins and hence determining the development of hypersaline conditions and associated oolitic microbial and evaporitic facies in Hamelin Pool and L'Haridon Bight. Moreover, this system has a critical role in producing, sequestering and storing organic carbon.